Upaya Guru Dalam Meningkatkan Minat Belajar Siswa Melalui Metode Gallery Walk Pada Pembelajaran Fiqih Kelas X SMA Muhammadiyah 1 Karanganyar - Rahmawati, Anggraini Putri; Jinan, Mutohharun (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to understand the teacher's efforts in increasing students' interest in learning through the application of the Gallery Walk method in learning fiqh in class X SMA Muhammadiyah 1 Karanganyar. This research uses a qualitative approach with a case study method. Teachers try to increase students' interest in learning by using the Gallery Walk learning method. This method involves students directly in the learning process. The application of this method aims to make the learning atmosphere not monotonous so that students feel interested in participating in learning, students are actively involved in learning as well. The results of this study showed a significant increase in student interest in learning, the level of student attention in participating in fiqh learning before this method was 60% to 75% after the application of this method. In addition, there is an increase in student interest from 65% to 80%. In addition, the application of this method also increased students' active involvement from 65% to 75% because they actively asked questions, discussed with the group. However, in applying the learning method the teacher experienced obstacles such as limited learning time of only 45 minutes and difficulty conditioning students. The solutions given include dividing the learning time into 2 meetings and giving consequences to students.